Pengaruh Kepemimpinan Transformasional terhadap Kinerja Karyawan dengan Kepuasan Kerja dan Organizational Citizenship Behavior sebagai Variabel Mediasi - Rasminingsih, Ni Kadek Nonik; JS, I Putu Wahyu Dwinata; Diputra, I Komang Suryadnya (Ekonomis: Journal of Economics and Business, 2024)
Correct and good management of human resources (HR) will get employees who have high skills and are reliable, so that the performance of the company's employees will be better and can achieve company goals optimally. This research aims to analyze the influence of transformational leadership, job satisfaction, and organizational citizenship behavior. The number of samples used was 237 respondents in BPD Bali Province. The data analysis technique was carried out using Path Analysis (SEM PLS). The results of the research prove that transformational leadership has a positive and significant influence on employee performance, job satisfaction does not have a significant positive influence on employee performance, job satisfaction does not have a significant positive influence on employee performance, job satisfaction does not have a significant positive influence on employee satisfaction, organizational citizenship behavior has a significant positive influence on employee performance, transformational leadership has a significant positive influence on organizational citizenship behavior, the influence of transformational leadership on employee performance is not mediated by job satisfaction and transformational leadership has a positive and significant influence on employee performance which is mediated by the organizational citizenship behavior variable.